Interaction of N-succinyl-diaminopimelate desuccinylase with flavonoids - Diaz Sanchez, Angel Gabriel (2020)
DapE is an enzyme that belongs to the meso-diaminopimelate/Lysine pathway. It is recognized as an antimicrobial target, hence compounds that inhibit its catalytic activity are required. The principal features considered in the selection of potential inhibitors for this enzyme are compounds containing metal binding groups that could block access of the substrate to the Zinc metal centers and/or block the assembly of the oxyanion hole. We show the interaction of DapE from Enterococcus faecium, Staphylococcus aureus, Klebsiella aerogenes, Pseudomonas aeruginosa and Escherichia coli with flavonoids: quercetin, catechin, luteolin, rutin and hesperidin. Flavonoids contain several oxygen atoms distributed along their structure in a pattern that may be considered for the development of new antibiotics. Docking experiments suggest that these compounds containing metal binding groups that interact with metal centers of DapE and binding experiments indicate that glycoside flavonoids are preferred by DapE.